Femen in the current Spanish political context: feminist activism and counterhegemonic modes of representation. - Núñez Puente, Sonia (Journal of Spanish Cultural Studies, 2018)
The purpose of this article is to address Femen’s media-based activism in Spain, focusing, on the one hand, on the lack of understanding of Femen’s activist methods by broad swaths of institutionalized feminism, and on the other, on their activism’s repercussions in the broader debates in the current Spanish political context. In order to achieve these objectives, I work from the premise that the use of politics of the body linked to counterhegemonic representational modes impacts the possibilities and reach of Femen’s activist practices. At the same time, paradoxically, these practices are situated in the politics of the street and bodies in alliance that have determined new forms of political practice. I will argue that these new feminist political actions – which are articulated through processes of mediation, culture jamming and recontextualization – are defined not so much by the effectiveness of the new cultural practices one finds in contemporary activism, but by how they become part of what is now called awkward politics.